Carcinoma of Left Breast with Secondary Metastatic Cord Compression- A Case Report (TAJ: Journal of Teachers Association, 2009)
A 45-year-old female presented with weakness of lower extremities with history of simple mastectomy one year back. On myelographic examination showed complete block at mid thoracic level which is extra-dural in nature. On operation extra-dural large mass compressing the spinal cord at T5 level was detected.   doi: 10.3329/taj.v18i1.3306 TAJ 2005; 18(1): 51-52